Respiratory tract deposition of inhaled roadside ultrafine refractory particles in a polluted megacity of South-East Asia - Kecorius, Simonas (Animo Repository, 2019)
Recent studies demonstrate that Black Carbon (BC) pollution in economically developing megacities remain higher than the values, which the World Health Organization considers to be safe. Despite the scientific evidence of the degrees of BC exposure, there is still a lack of understanding on how the severe levels of BC pollution affect human health in these regions. We consider information on the respiratory tract deposition dose (DD) of BC to be essential in understanding the link between personal exposure to air pollutants and corresponding health effects. In this work, we combine data on fine and ultrafine refractory particle number concentrations (BC proxy), and activity patterns to derive the respiratory tract deposited amounts of BC particles for the population of the highly polluted metropolitan area of Manila, Philippines. We calculated the total DD of refractory particles based on three metrics: refractory particle number, surface area, and mass concentrations. The calculated DD of total refractory particle number in Metro Manila was found to be 1.6 to 17 times higher than average values reported from Europe and the U.S. In the case of Manila, ultrafine particles smaller than 100 nm accounted for more than 90% of the total deposited refractory particle dose in terms of particle number. This work is a first attempt to quantitatively evaluate the DD of refractory particles and raise awareness in assessing pollution-related health effects in developing megacities. We demonstrate that the majority of the population may be highly affected by BC pollution, which is known to have negative health outcomes if no actions are taken to mitigate its emission. For the governments of such metropolitan areas, we suggest to revise currently existing environmental legislation, raise public awareness, and to establish supplementary monitoring of black carbon in parallel to already existing PM 10 and PM 2.5 measures. © 2019